Grain size and mechanical properties of metals subjected to equal channel angular pressing (ECAP) process - M. A., Hisyam; Dayangku Noorfazidah, Awang Sh'ri (Centre for Advanced Research on Energy (CARe), 2017)
Equal Channel Angular Pressing (ECAP) is one of the most efficient technique in metal forming process which induced severe plastic deformation (SPD) to produce bulk ultrafine-grained metals. This research used Titanium CP Grade 2 and Aluminum Alloy 6061 to investigate the grain size and mechanical properties of both materials after ECAP process. The materials were extruded through die channel! angel of 126 internal and 10 external under pressure 60 bar. The result shows that there is significant increase in grain refinement and hardness after ECAP process for both materials